2021
DOI: 10.3390/ijms22031102
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Therapy for Alzheimer′s Disease Memory Impairment Attenuation

Abstract: Currently, there is no cure for Alzheimer’s disease (AD) in humans; treatment is symptomatic only. Aging of the population, together with an unhealthy diet and lifestyle, contribute to the steady, global increase of AD patients. This increase creates significant health, societal and economical challenges even for the most developed countries. AD progresses from an asymptomatic stage to a progressively worsening cognitive impairment. The AD cognitive impairment is underpinned by progressive memory impairment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Research has shown that over expressed normal Tau and/or overexpressed mutant Tau in neurons become hyper phosphorylated, causing oxidative stress, mitochondrial dysfunction, synaptic deprivation, and neuronal damage. This was discovered using brain tissues from transgenic mouse models of Tau, APP/PS1, and 3XAD.Tg (Ribarič, 2021). Several research groups have reported oxidative damage, defective mitochondrial activities, disrupted calcium homeostasis, and defective mitochondrial function in 3xTg-AD mice 43-47 and APP/PS1,48, both of which are mouse models that produce hyper phosphorylated Tau, supporting the hypothesis that phosphorylated Tau is involved in mitochondrial dysfunction and synaptic damage in AD [26].…”
Section: Role Of Tau and Phosphorylated Tau In Admentioning
confidence: 80%
See 1 more Smart Citation
“…Research has shown that over expressed normal Tau and/or overexpressed mutant Tau in neurons become hyper phosphorylated, causing oxidative stress, mitochondrial dysfunction, synaptic deprivation, and neuronal damage. This was discovered using brain tissues from transgenic mouse models of Tau, APP/PS1, and 3XAD.Tg (Ribarič, 2021). Several research groups have reported oxidative damage, defective mitochondrial activities, disrupted calcium homeostasis, and defective mitochondrial function in 3xTg-AD mice 43-47 and APP/PS1,48, both of which are mouse models that produce hyper phosphorylated Tau, supporting the hypothesis that phosphorylated Tau is involved in mitochondrial dysfunction and synaptic damage in AD [26].…”
Section: Role Of Tau and Phosphorylated Tau In Admentioning
confidence: 80%
“…Poly (ethylenimine), poly (alkylcyanoacrylates), poly (amidoamine) dendrimers, poly (-caprolactone), poly (D, L-lactic acid) (PLA), poly (lactic-co-glycolic acid) (PLGA), polyethylene glycol (PEG), and polyesters made of poly (lactic acid) (PLA) are a few examples of synthetic polymer-based NPs. Gold, silica, and carbon are a few examples of inorganic materials for medicinal NPs [20]. Recent research suggests that particular sizes, shapes, and types of sulfur nanoparticles (SNPs) can have the moderating effect against AD pathogenesis, despite the potential implications of certain types of nanoparticles in accelerating AD development [21].…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnologies lies primarily in their use as diagnostic tools, drug delivery, and therapy [28][29][30]. Modification of NPs surfaces significantly affects the physical, chemical, and biological nature of entire molecules in biological systems [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the potential of nanoparticles for medical Biotechnologies lies primarily in their use as diagnostic tools, drug delivery, and therapy [28][29][30]. Modification of NPs surfaces significantly affects the physical, chemical, and biological nature of entire molecules in biological systems [31].…”
Section: Discussionmentioning
confidence: 99%